The Prevalence and Associations of Psychiatric Disorder in Children in Kerala, South India - Richard Hackett Latha Hackett Preeta Bhakta (J. Child Psychol. Psychiat. Vol. 40, No. 5, pp. 801807, 1999, 1999)
This study aimed to identify the prevalence and associations of childhood psychiatric disorder in Calicut District, South India. Among 1403 children aged 8 to 12 years selected by random cluster sampling, a projected prevalence of 94 (95 CI 79108) was found. Associations of disorder with male sex, the Muslim religion, lower social class, less parental education, school failure, and impaired reading and vocabulary were found, but not with malnutrition or perinatal problems. The similarity to associations of disorder in Western studies was noted. The discussion focuses on the validity of comparisons of prevalence across cultures